Integrated genome and gene diversity analyses of bacterial genera in metagenomic data - Gabas, Mariana Louise; Barrios Solano, Arthur Henrique; Setubal, João Carlos (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2025)
We present an analysis of subspecies diversity of the bacterial genera Xanthomonas, Acinetobacter, and Stenotrophomonas present in the MetaSUB metagenomic dataset. We used the simulated rarefaction curve technique along with the non-parametrics estimators Chao1, Chao2, Jackknife, ICE, and ACE, to estimate the total number of subspecies (subgroups) within the MetaSUB dataset. Subgroup is an operational concept that can be used to distinguish between genomes from the same species. For Xanthomonas, our results suggest that MetaSUB may have more subgroups than currently known; for Acinetobacter, the number of estimated subgroups is lower than the known number; and for Stenotrophomonas, the estimates and the known number are the same. A comparison of the pangenomes of Xanthomonas obtained from our genome database and that from MetaSUB showed that the genic diversity in MetaSUB is much lower than the database diversity, suggesting that urban environments constrain the genic diversity compared to the biosphere as a whole.